Downregulation of SPARC is associated with epithelial-mesenchymal transition and low differentiation state of biliary tract cancer cells - Aghamaliyev, Ughur; Gaitantzi, Haristi; Cai, Chen; Ebert, Matthias; Breitkopf-Heinlein, Katja (European surgical research, 2019)
Background: Biliary tract cancers (BTCs) have a poor prognosis. BTCs are characterized by a prominent desmoplastic reaction which possibly contributes to the aggressive phenotype of this tumor. The desmoplastic reaction includes excessive production and deposition of extracellular matrix proteins such as periostin, secreted protein acidic and rich in cysteine (SPARC), thrombospondin-1, as well as accumulation of α-smooth muscle actin-positive cancer-associated fibroblasts and immune cells, secreting growth factors and cytokines including transforming growth factor (TGF)-β. In the present study, we investigated the expression of SPARC in BTC as well as its possible regulation by TGF-β. Methods: Expression levels of Sparc, TGF-β1 and its receptor ALK5 were evaluated by quantitative real-time PCR in 6 biliary tract cell lines as well as 1 immortalized cholangiocyte cell line (MMNK-1). RNAs from tumor samples of 7 biliary tract cancer patients were analyzed for expression of Sparc, TGF-β type II receptor (TbRII) as well as Twist and ZO-1. MMNK-1 cells were stimulated with TGF-β for 24 h, and Sparc, ZO-1 and E-Cadherin expressions were determined. The presence of SPARC protein was analyzed by immunohistochemistry in tumor specimens from 10 patients. Results: When comparing basal Sparc transcript levels in diverse BTC cell lines to MMNK-1 cells, we found that it was strongly downregulated in all cancer cell lines. The remaining expression levels were higher in highly differentiated cell lines (CCSW1, MZChA1, MZChA2 and TFK-1) than in less differentiated and undifferentiated ones (BDC, SKChA1). Expression of Sparc in BTC patient samples showed a significant positive correlation with expression of the epithelial marker ZO-1. In contrast, the mesenchymal marker Twist and the TbRII showed a trend of negative correlation with expression of Sparc in these samples. TGF-β exposure significantly downregulated Sparc expression in MMNK-1 cholangiocytes in vitro in parallel to downregulation of epithelial markers (E-Cadherin and ZO-1). Finally, SPARC immunostaining was performed in 10 patient samples, and the correlation between absence of SPARC and survival times was analyzed. Conclusions: These data imply that a decrease in SPARC expression is correlated with dedifferentiation of BTC cells resulting in enhanced EMT being possibly mediated by TGF-β. Thereby SPARC levels might be a marker for individual prognosis of a patient, and strategies aiming at inhibition of SPARC downregulation might have potential for new future therapies.